Islamic Business Ethics in Online Commerce: A Perspective from Maqashid Shariah by Imam Haramain - Albar, Kholid; Abubakar, Achmad; Arsyad, Aisyah (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2023)
This research aims to understand the maslahah principle in the maqashid sharia concept, which is used as a basis for making laws for justice and prosperity, and how this principle is applied in Islamic economics and business. This research uses a qualitative approach with data analysis techniques such as field notes to conclude. This research tool measures events and collects data based on information from the parties involved (sellers and buyers). The data collected is based on observations of consumers and sellers' followers. The research results show that in online buying and selling transaction activities, it is essential to pay attention to the principles of justice in order to avoid things that can harm other parties and can be held accountable. In this case, the mu'amalah relationship that is the main thing in transactions in online buying and selling is the contract and